Cesium lead halide perovskite quantum dot glass optical fiber and preparation method thereof

The cesium lead halide perovskite quantum dot borosilicate glass fiber is prepared by high-temperature melt lateral drawing method, which solves the problem of insufficient coverage of perovskite quantum dot glass fiber in the visible band in the prior art, and realizes tunable and efficient quantum dot crystallization of the optical fiber fluorescence wavelength.

CN119661086AActive Publication Date: 2025-03-21ZHEJIANG UNIV OF TECH

Patent Information

Application Number
CN202510179868.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-19
Publication Date
2025-03-21
Estimated Expiration
2045-02-19

AI Technical Summary

Technical Problem

In the prior art, there are few researches on perovskite quantum dot glass fibers, especially in terms of luminescence wavelength coverage in the visible band, which limits its further development in the fields of optical communications and other fields.

Method used

The high-temperature melt transverse wire drawing method is used to prepare cesium lead halide perovskite quantum dot borosilicate glass fiber. By regulating the glass network structure, halogen components and heat treatment conditions, the optical fiber fluorescence wavelength is tunable in the visible band.

Benefits of technology

Controllable crystallization and uniform distribution of perovskite quantum dot glass fibers are achieved. The optical fiber fluorescence wavelength covers the visible band of 450-710nm, and has high fluorescence quantum yield and narrowband photoluminescence performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119661086A_ABST
    Figure CN119661086A_ABST
Patent Text Reader

Abstract

The invention discloses a cesium lead halide perovskite quantum dot glass optical fiber and a preparation method thereof. Component elements of the perovskite quantum dots are added into a borosilicate glass system to generate Cs < + >, Pb < 2 + > and halide ions, reagents are adjusted according to the types of the needed perovskite quantum dots, and the optical fiber is obtained after sufficient grinding, high-temperature melting, cooling and wire drawing. Then, the glass optical fiber with the perovskite quantum dots uniformly distributed in size and density can be obtained through a heat treatment process; the preparation method is simple, the price is low, quantum dot crystallization is controllable, and the prepared optical fiber has very strong adjustability of fluorescence peaks and broadband and has application prospects in optical fiber lasers.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of optical communication technology and nano material preparation, and in particular to a cesium lead halide perovskite quantum dot glass optical fiber and a preparation method thereof. Background Art

[0002] In recent years, glass optical fiber has been widely studied due to its many advantages such as low loss, high bandwidth, and strong anti-interference ability. It has an irreplaceable position in the fields of optical communications, lasers, sensing, and lighting.

[0003] Quantum dots are a type of low-dimensional semiconductor material with a lattice structure. Their size is at the nanometer level, usually ranging from a few nanometers to tens of nanometers. Due to the quantum confinement effect caused by their extremely small size, quantum dots exhibit special optical, electrical and magnetic properties. Among them, perovskite quantum dots have attracted much attention due to their excellent photoelectric properties and broad application prospects. Perovskite refers to an oxide with a general molecular formula of ABO3, in which the A position is usually occupied by a metal ion with a larger radius, while the B position is occupied by a metal ion with a smaller radius. In addition, other ions with similar radii or valences can also be embedded in this structure while keeping the crystal structure unchanged. Cesium lead halide perovskite quantum dots usually refer to semiconductor materials with the chemical formula CsPbX3 (X=Cl, Br, I). In this structure, Cs + Occupies the A site of perovskite, Pb 2+ Occupying the B position of perovskite, halogen elements (Cl - , Br - , I - ) occupies the O position of perovskite. Perovskite quantum dots have many advantages, such as high fluorescence quantum yield, narrow-band photoluminescence, wide wavelength absorption, etc. In addition, by adjusting the type and proportion of halogen element X, luminescence covering the entire visible light range (400-750nm) can be achieved under ultraviolet light excitation.

[0004] At present, the research on quantum dot optical fiber is mainly focused on the near-infrared band, while the research on perovskite quantum dot glass optical fiber is relatively small, which seriously restricts its further development. Based on this, the present invention prepares CsPbCl with a luminescent wavelength covering 450-710nm x Br 3-x and CsPbBr x I 3-xPerovskite quantum dot glass fiber. At present, there are mainly the following methods for preparing quantum dot glass fiber: The first is to prepare PbSe quantum dot glass fiber by vertical drawing of glass melt. This process is only used for the preparation of near-infrared PbSe quantum dot glass fiber and does not involve perovskite quantum dot fiber. The second is to prepare quantum dot glass fiber by double crucible method, in which the core glass melt doped with quantum dots and the cladding glass melt not doped with quantum dot components are poured into the inner crucible and the outer crucible respectively. After heating the crucible to a certain temperature, the glass melt flows down together to form a precursor fiber, which is then annealed at different temperatures to precipitate quantum dots. This preparation process does not involve perovskite quantum dot glass fiber. The third is to prepare quantum dot glass fiber by tube-rod method, in which relatively stable silicate glass is selected as the core material, heated to soften, and then the fiber is drawn under the action of gravity, and then the fiber is annealed near the glass transition temperature to finally obtain quantum dot glass fiber. This preparation process does not involve perovskite quantum dot glass fiber. The fourth method is to prepare quantum dot glass optical fiber by melt-in-tube co-drawing. This method first prepares a quantum dot-doped glass rod, which is then polished as the core glass; then prepares a cladding glass without quantum dot components, inserts the core glass into the cladding glass to obtain an optical fiber preform, and then draws the preform in a drawing tower. This method has been used to prepare CsPbCl x Br 3-x and CsPbBr3 perovskite quantum dot glass optical fiber, the glass system is phosphate glass.

[0005] The present invention provides a high-temperature melt transverse drawing method for preparing cesium lead halide perovskite quantum dot borosilicate glass optical fiber, and achieves tunable optical fiber fluorescence wavelength in the visible band by regulating the glass network structure, halogen components and heat treatment conditions. Summary of the invention

[0006] The present invention aims to provide a cesium lead halide perovskite quantum dot glass optical fiber and a preparation method thereof. The present invention avoids the problem of uncontrollable crystallization of quantum dots in the process of preparing optical fibers in the prior art, and has a simple method, low raw material price, controllable quantum dot size and density, and a luminescent wavelength covering the entire visible band.

[0007] The idea of ​​the present invention is: firstly, the component elements of perovskite quantum dots are added to the borosilicate glass system to generate Cs + , Pb 2+ and halogen ions, and the reagents are adjusted according to the type of perovskite quantum dots required. After sufficient grinding, high-temperature melting, and cooling and drawing, the optical fiber is obtained. Then, after a heat treatment process, a glass optical fiber with uniform distribution of perovskite quantum dots in size and density can be obtained.

[0008] The technical solution of the present invention is as follows:

[0009] A cesium lead halide perovskite quantum dot glass optical fiber is made of the following raw materials in molar percentage:

[0010] SiO222~37%

[0011] B2O323~38%

[0012] ZnO 15~25%

[0013] CaF20~5%

[0014] Cs2CO35~13%

[0015] PbCl20~2%

[0016] NaCl 0~7%

[0017] PbBr20~2%

[0018] NaBr 0~7%

[0019] PbI20~2%

[0020] NaI 0~7%

[0021] Among them, PbCl2, PbBr2, and PbI2 are not 0 at the same time, and NaCl, NaBr, and NaI are not 0 at the same time;

[0022] All raw materials add up to 100%.

[0023] The optical fiber of the present invention is doped with CsPbCl x Br 3-x and / or CsPbBr x I 3-x (x=0~3) Perovskite quantum dot glass optical fiber is preferably made of the following raw materials in molar percentage:

[0024] SiO225~34%

[0025] B2O326~35%

[0026] ZnO 18~22%

[0027] CaF20.5~1.5%

[0028] Cs2CO35~9%

[0029] PbCl20~1.6%

[0030] NaCl 0~6.8%

[0031] PbBr20~1.6%

[0032] NaBr 0~6.8%

[0033] PbI20~1.6%

[0034] NaI 0~6.8%

[0035] Among them, PbCl2, PbBr2, and PbI2 are not 0 at the same time, and NaCl, NaBr, and NaI are not 0 at the same time;

[0036] All raw materials add up to 100%.

[0037] The preparation method of the cesium lead halide perovskite quantum dot glass optical fiber of the present invention is as follows:

[0038] (1) Grinding and mixing: taking the raw materials according to the proportion, grinding and mixing them evenly in an agate mortar to obtain a mixture;

[0039] Grind for 15-20 minutes;

[0040] When adjusting the type and ratio of halogen elements, the molar percentage of B2O3 and SiO2 needs to be changed to obtain the optimal crystallization conditions (see the embodiments of the present invention for details, which provide the optimal crystallization conditions for different perovskite quantum dot optical fibers);

[0041] (2) High-temperature melting: Pour the ground mixture into a sealed corundum crucible and place it in a muffle furnace for melting to obtain a glass melt;

[0042] The melting temperature is 1100~1200℃ and the melting time is 10~30min, thus a uniformly mixed high-temperature glass melt can be obtained;

[0043] (3) Cooling and drawing: When the glass melt is cooled to a viscous state, the corundum crucible is placed horizontally on a high-temperature resistant platform, and a wire is drawn horizontally from the glass melt using an iron wire to obtain a glass optical fiber precursor;

[0044] When the glass melt is cooled to 650-850℃, it becomes viscous, and the moderate viscosity is conducive to horizontal drawing;

[0045] The specific operation of transverse wire drawing is as follows: insert the iron wire into the glass melt, and ensure that one end of the iron wire is wrapped by the glass melt, and then pull it out transversely, and a glass optical fiber precursor can be obtained between the iron wire and the crucible;

[0046] (4) Heat treatment: placing the glass fiber precursor in a quartz boat and placing it in a vacuum tube furnace for heat treatment to precipitate perovskite quantum dots, and then waiting for the tube furnace to cool to room temperature to obtain the cesium lead halide perovskite quantum dot glass fiber;

[0047] The heat treatment temperature is 450~550℃ and the time is 2~10h.

[0048] The technical principles of the present invention are as follows:

[0049] In the raw material composition of the present invention, SiO2 and B2O3 are network formers, and their main function is to form a glass network structure. By adjusting the molar ratio of SiO2 and B2O3, the crystallization of perovskite quantum dots can be promoted or inhibited, thereby affecting the luminescence performance of glass optical fiber; ZnO is a network intermediate, which is helpful for the synthesis of perovskite quantum dots and the uniformity of quantum dot size distribution; CaF2 is used to reduce the transition temperature of glass to promote the crystallization of perovskite quantum dot glass; Cs2CO3, PbCl2, NaCl, PbBr2 and NaBr are used as CsPbCl x Br 3-x The introduction body of quantum dots; Cs2CO3, PbBr2, NaBr, PbI2 and NaI as CsPbBr x I 3-x The introduction of quantum dots and perovskite quantum dot optical fibers prepared using different raw materials can achieve luminescence in the 450~710nm band.

[0050] The key point of the present invention is that the crystallization of perovskite quantum dots in glass optical fiber can be controlled and evenly distributed. During the optical fiber drawing process, transverse drawing can prevent the quantum dots from being deposited at the bottom of the optical fiber. In addition, because the glass melt is drawn very thinly, it cools down quickly, so that the quantum dots do not have time to crystallize, thereby reducing the uncontrollable crystallization of the quantum dots. The size of the perovskite quantum dots can be controlled by the heat treatment process. The crystallization of glass at high temperature includes two stages: nucleation and growth. At a suitable temperature, the higher the heat treatment temperature, the faster the growth rate of the crystal nucleus, and the larger the size of the perovskite quantum dots. The longer the heat treatment time, the larger the size of the perovskite quantum dots. Therefore, by adjusting the temperature and time of the heat treatment, perovskite quantum dots of different sizes can be obtained, and according to the quantum size effect, perovskite quantum dot glass optical fibers with different luminescence wavelengths can be obtained.

[0051] Compared with the prior art, the beneficial effects of the present invention are mainly reflected in:

[0052] The method for preparing cesium lead halide perovskite quantum dot glass optical fiber of the present invention is simple, low-cost, and the crystallization of quantum dots is controllable. The prepared optical fiber has strong fluorescence peak and broadband adjustability, and has application prospects in optical fiber lasers. BRIEF DESCRIPTION OF THE DRAWINGS

[0053] Figure 1 : Fluorescence emission spectrum of the CsPbCl2Br1 quantum dot glass optical fiber of Example 1.

[0054] Figure 2 : Fluorescence emission spectrum of the CsPbCl1Br2 quantum dot glass optical fiber of Example 2.

[0055] Figure 3 : Fluorescence emission spectrum of the CsPbBr3 quantum dot glass optical fiber of Example 3.

[0056] Figure 4 : Fluorescence emission spectrum of the CsPbBr1I2 quantum dot glass optical fiber of Example 4.

[0057] Figure 5 : Fluorescence emission spectrum of the CsPbI3 quantum dot glass optical fiber of Example 5.

[0058] Figure 6 : Schematic diagram of the preparation process of the present invention. DETAILED DESCRIPTION

[0059] The present invention is further described below by means of specific embodiments, but the protection scope of the present invention is not limited thereto.

[0060] Embodiment 1:

[0061] According to the molar ratio of SiO2:B2O3:ZnO:CaF2:Cs2CO3:PbCl2:NaCl:PbBr2:NaBr=31:29:20:1:7:1.07:4.53:0.53:2.27, weigh 3.33g of analytically pure SiO2, 3.61g of B2O3, 2.91g of ZnO, 0.14g of CaF2, 4.09g of Cs2CO3, 0.53g of PbCl2, 0.47g of NaCl, 0.35g of PbBr2, and 0.42g of NaBr. The above chemical raw materials were ground thoroughly in a mortar, placed in a sealed corundum crucible and moved into a high-temperature muffle furnace, melted at 1200°C for 20 minutes to obtain a glass melt. After the melt was cooled to 730°C and had a moderate viscosity, an iron wire was inserted into the glass melt and quickly pulled out horizontally to obtain a CsPbCl2Br1 quantum dot glass optical fiber precursor.

[0062] Then, the fiber precursor is placed in a quartz boat and moved into a vacuum tube furnace, where it is heated from room temperature to 470°C and heat treated for 8 hours to precipitate CsPbCl2Br1 quantum dots. After the heat treatment time is over and the tube furnace is cooled to room temperature, CsPbCl2Br1 quantum dot glass fiber is obtained. The prepared fiber fluorescence emission spectrum is shown in Figure 2. Figure 1As shown, its central wavelength is 476nm and its full width at half maximum is 20nm.

[0063] Embodiment 2:

[0064] According to the molar ratio of SiO2:B2O3:ZnO:CaF2:Cs2CO3:PbCl2:NaCl:PbBr2:NaBr=30:30:20:1:7:0.53:2.27:1.07:4.53, weigh 3.33g of analytically pure SiO2, 3.86g of B2O3, 3.01g of ZnO, 0.14g of CaF2, 4.22g of Cs2CO3, 0.27g of PbCl2, 0.25g of NaCl, 0.72g of PbBr2, and 0.86g of NaBr. The above chemical raw materials were ground thoroughly in a mortar, placed in a sealed corundum crucible and moved into a high-temperature muffle furnace, melted at 1200°C for 20 minutes to obtain a glass melt. After the melt was cooled to 730°C and had a moderate viscosity, an iron wire was inserted into the glass melt and quickly pulled out horizontally to obtain a CsPbCl1Br2 quantum dot glass optical fiber precursor.

[0065] Then, the fiber precursor is placed in a quartz boat and moved into a vacuum tube furnace, where it is heated from room temperature to 480°C and heat treated for 4 hours to precipitate CsPbCl1Br2 quantum dots. After the heat treatment time is over and the tube furnace is cooled to room temperature, CsPbCl1Br2 quantum dot glass fiber is obtained. The prepared fiber fluorescence emission spectrum is shown in Figure 2. Figure 2 As shown, its central wavelength is 500nm and its full width at half maximum is 18nm.

[0066] Embodiment 3:

[0067] According to the molar ratio of SiO2: B2O3: ZnO: CaF2: Cs2CO3: PbBr2: NaBr = 30: 30: 20: 1: 7: 1.6: 6.8, 3.33g of analytically pure SiO2, 3.86g of B2O3, 3.01g of ZnO, 0.14g of CaF2, 4.22g of Cs2CO3, 1.09g of PbBr2, and 1.29g of NaBr were weighed. After the above chemical raw materials were fully ground in a mortar, they were placed in a sealed corundum crucible and moved into a high-temperature muffle furnace, melted at 1200°C for 20min to obtain a glass melt, and after the melt was cooled to 730°C with a moderate viscosity, an iron wire was inserted into the glass melt and quickly pulled out horizontally to obtain a CsPbBr3 quantum dot glass fiber precursor.

[0068] Then, the fiber precursor is placed in a quartz boat and moved into a vacuum tube furnace, where it is heated from room temperature to 490°C and heat treated for 4 hours to precipitate CsPbBr3 quantum dots. After the heat treatment time is over and the tube furnace is cooled to room temperature, CsPbBr3 quantum dot glass fiber is obtained. The prepared fiber fluorescence emission spectrum is shown in Figure 2. Figure 3 As shown, its central wavelength is 512nm and its full width at half maximum is 22nm.

[0069] Embodiment 4:

[0070] According to the molar ratio of SiO2:B2O3:ZnO:CaF2:Cs2CO3:PbBr2:NaBr:PbI2:NaI=26:34:20:1:7:0.53:2.27:1.07:4.53, weigh 2.86g of analytical pure SiO2, 4.33g of B2O3, 2.98g of ZnO, 0.14g of CaF2, 4.17g of Cs2CO3, 0.36g of PbBr2, 0.43g of NaBr, 0.90g of PbI2 and 1.24g of NaI. The above chemical raw materials were ground thoroughly in a mortar, placed in a sealed corundum crucible and moved into a high-temperature muffle furnace, melted at 1200°C for 20 minutes to obtain a glass melt. After the melt was cooled to 730°C and had a moderate viscosity, an iron wire was inserted into the glass melt and quickly pulled out horizontally to obtain a CsPbBr1I2 quantum dot glass optical fiber precursor.

[0071] Then, the fiber precursor is placed in a quartz boat and moved into a vacuum tube furnace, where it is heated from room temperature to 520°C and heat treated for 4 hours to precipitate CsPbBr1I2 quantum dots. After the heat treatment time is over and the tube furnace is cooled to room temperature, CsPbBr1I2 quantum dot glass fiber is obtained. The prepared fiber fluorescence emission spectrum is shown in Figure 2. Figure 4 As shown, its central wavelength is 624nm and its full width at half maximum is 45nm.

[0072] Embodiment 5:

[0073] According to the molar ratio of SiO2: B2O3: ZnO: CaF2: Cs2CO3: PbI2: NaI = 25: 35: 20: 1: 7: 1.6: 6.8, 2.78g of analytically pure SiO2, 4.51g of B2O3, 3.01g of ZnO, 0.14g of CaF2, 4.22g of Cs2CO3, 1.36g of PbI2, and 1.88g of NaI were weighed. After the above chemical raw materials were fully ground in a mortar, they were placed in a sealed corundum crucible and moved into a high-temperature muffle furnace, melted at 1200°C for 15min to obtain a glass melt, and after the melt was cooled to 730°C with a moderate viscosity, an iron wire was inserted into the glass melt and quickly pulled out horizontally to obtain a CsPbI3 quantum dot glass fiber precursor.

[0074] Then, the fiber precursor is placed in a quartz boat and moved into a vacuum tube furnace, where it is heated from room temperature to 510°C and heat treated for 4 hours to precipitate CsPbI3 quantum dots. After the heat treatment time is over and the tube furnace is cooled to room temperature, CsPbI3 quantum dot glass fiber is obtained. The prepared fiber fluorescence emission spectrum is shown in Figure 2. Figure 5 As shown, its central wavelength is 688nm and its full width at half maximum is 35nm.

Claims

1. A cesium lead halide perovskite quantum dot glass optical fiber, characterized in that: Made from the following raw materials in mole percentage: SiO222~37% B2O323~38% ZnO 15~25% CaF20~5% Cs2CO35~13% PbCl20~2% NaCl 0~7% PbBr20~2% NaBr 0~7% PbI20~2% NaI 0~7% Among them, PbCl2, PbBr2, and PbI2 are not 0 at the same time, and NaCl, NaBr, and NaI are not 0 at the same time; All raw materials add up to 100%.

2. The cesium lead halide perovskite quantum dot glass optical fiber according to claim 1, characterized in that: Made from the following raw materials in mole percentage: SiO225~34% B2O326~35% ZnO 18~22% CaF20.5~1.5% Cs2CO35~9% PbCl20~1.6% NaCl 0~6.8% PbBr20~1.6% NaBr 0~6.8% PbI20~1.6% NaI 0~6.8% Among them, PbCl2, PbBr2, and PbI2 are not 0 at the same time, and NaCl, NaBr, and NaI are not 0 at the same time; All raw materials add up to 100%.

3. The cesium lead halide perovskite quantum dot glass optical fiber according to any one of claims 1 or 2, characterized in that: Optical fiber doped with CsPbCl x Br 3-x and / or CsPbBr x I 3-x , x=0~3.

4. The method for preparing cesium lead halide perovskite quantum dot glass optical fiber according to any one of claims 1 or 2, characterized in that: The preparation method is as follows: (1) Grinding and mixing: taking the raw materials according to the proportion, grinding and mixing them in an agate mortar to obtain a mixture; (2) High-temperature melting: Pour the ground mixture into a sealed corundum crucible and place it in a muffle furnace for melting to obtain a glass melt; (3) Cooling and drawing: When the glass melt is cooled to a viscous state, the corundum crucible is placed horizontally on a high-temperature resistant platform, and a wire is drawn horizontally from the glass melt using an iron wire to obtain a glass optical fiber precursor; (4) Heat treatment: The glass fiber precursor is placed in a quartz boat and placed in a vacuum tube furnace for heat treatment to precipitate perovskite quantum dots. After the tube furnace is cooled to room temperature, the cesium lead halide perovskite quantum dot glass fiber is obtained.

5. The preparation method according to claim 4, characterized in that: In step (2), the melting temperature is 1100-1200° C., and the melting time is 10-30 min.

6. The preparation method according to claim 4, characterized in that: In step (3), when the glass melt is cooled to 650-850° C., it becomes viscous, and the moderate viscosity is conducive to transverse wire drawing.

7. The preparation method according to claim 4, characterized in that: In step (3), the operation of transverse wire drawing is as follows: insert the iron wire into the glass melt and ensure that one end of the iron wire is wrapped by the glass melt, and then pull it out transversely to obtain a glass optical fiber precursor between the iron wire and the crucible.

8. The preparation method according to claim 4, characterized in that: In step (4), the heat treatment temperature is 450-550° C. and the time is 2-10 hours.

Citation Information

Patent Citations

  • Mode-locked optical fiber laser which takes lead selenide quantum dot as saturable absorber

    CN107069413A

  • PbSe quantum dot doped sodium aluminum boron germanate glass optical fiber

    CN112499979A

  • Biphase quantum dot microcrystalline glass and preparation method and application thereof

    CN114920460A

  • Preparation method and application of perovskite quantum dot double-spectrum luminescent glass material

    CN118930046A

  • Optical amplification glass and optical waveguide

    JP2004307306A

Cited By

  • Rare earth ion doped CsPbX3 perovskite quantum dot glass optical fiber as well as preparation method and application thereof

    CN121779004A